Iman dan Tauhid: Kunci Menuju Keselamatan Dunia dan Akhirat - Melani Putri; Ratu Aisyah; Muhammad Zaki; Abdee Putra Wiguna; Wismanto Wismanto (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
Islam is a divine religion that contains the law of Allah سُبْحَانَهُ وَ تَعَالَى, the Lord of the universe. Islamic teachings are universal and intended for all creatures both on earth and in the sky. In addition, Islamic teachings are flexible (easily adapted) according to the development of the times. In the modern era like today, there are many conveniences that humans can feel as a result of the development of technology and information. This can have positive and negative impacts on human life. If humans cannot control their behavior in this modern life, humans can fall into the abyss of humiliation and disgrace. That is why religion plays a very important role in guiding humans, especially in this modern era. This study aims to discuss how Islam guarantees safety in life in the world and in the hereafter in the context of modern life. This discussion is intended to find out how humans should behave, in order to achieve safety in life not only in the world, but also safety in the hereafter. This study uses a literature study method, where researchers obtain data from library sources such as books, journals and other scientific publications. Data from these sources are then analyzed and concluded in order to obtain accurate data. The results of this study indicate that straight Faith and Tawhid are the keys to salvation in the world and the hereafter.